Tunable Bandpass Filter Using Series Connected Varactor Diodes. Issue 2 (4th March 2022) - Issa, H.; Wehbi, M.
Abstract : The paper presents a novel design of tunable third-order parallel-coupled line filter. The design is based on using short-circuited resonators loaded in series by varactor diodes. Integrating the varactor diodes in the middle of the resonator has made this design unique. It is shown that varying the internal capacitance the varactor diodes has a direct impact on tuning the odd-mode resonance frequency of the resonator. The proposed concept is validated by comparing theoretical equations to circuit simulations. Very good agreement is found. When the concept is applied to the design of a third-order parallel line-coupled filter, the obtained tuning range is ±27.3% (central frequency tuned between 1.74 and 3.05 GHz). In addition, the filter presents good electrical performance and compact size (73% surface miniaturization) with respect to the state of art results.